Effects of the US Foreign Policy Shifts on the Eastern Mediterranean Region - Savoğlu, Hatice (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
This thesis will evaluate how changes in US foreign policy during 2000s may affect the countries within the Eastern Mediterranean region. Recent shifts in the US Foreign Policy, where the US decided to lift the arms embargo on the Republic of Cyprus through the Eastern Mediterranean Security and Energy Partnership Act of 2019 could bolster the Greek Cypriot's power and reshape the geopolitical context. My hypothesis is that this recent foreign policy shift will increase tensions within Cyprus and between Cyprus and other nations in the Eastern Mediterranean region. As the United States makes its foreign policy decisions based on its self-interests, this research will touch up on the neo-realism of Kenneth Waltz and will be assessed through the offensive realism of John Mearsheimer. It will touch upon historical and recent events where the US used buck-passing strategies to achieve its national interests. The study will concentrate on how US foreign policy is formulated and the factors that influence US foreign policy choices. The design of the research will be based on qualitative analysis to identify perspectives of the major powers involved within the Eastern Mediterranean region. The limitation of this research is that alternative hypotheses can exist where the US decision to lift the arms embargo leads to tensions dissolving within the region or there being a much more even dynamic regarding the Cyprus Conflict. Overall, this thesis will provide insight into how recent US foreign policy shifts can shape the regional relations among the nations within the Eastern Mediterranean region and provide assumptions about possible future scenarios.

ÖZ: Bu tez, 2000’lerde ABD dış politikasındaki değişikliklerin Doğu Akdeniz bölgesindeki ülkeleri nasıl etkileyebileceğini değerlendirecektir. ABD'nin 2019 tarihli Doğu Akdeniz Güvenlik ve Enerji Ortaklığı Yasası aracılığıyla Kıbrıs Cumhuriyeti'ne yönelik silah ambargosunu kaldırmaya karar vermesiyle ABD Dış Politikasındaki son değişiklikler, Kıbrıslı Rumların gücünü artırabilir ve jeopolitik bağlamı yeniden şekillendirebilir. Benim hipotezim, bu son dış politika değişikliğinin Kıbrıs içinde ve Kıbrıs ile Doğu Akdeniz bölgesindeki diğer ülkeler arasındaki gerilimleri artıracağı yönünde. ABD dış politika kararlarını kendi çıkarları doğrultusunda aldığı için bu araştırmada Kenneth Waltz'un neo-realizmi ele alınacak ve John Mearsheimer'ın saldırgan realizmi üzerinden değerlendirilecektir. ABD'nin ulusal çıkarlarına ulaşmak için sorumluluğu başkalarına yükleme stratejilerini kullandığı tarihsel ve güncel olaylara değinilecek. Çalışma, ABD dış politikasının nasıl formüle edildiğine ve ABD dış politika tercihlerini etkileyen faktörlere odaklanacaktır. Araştırmanın tasarımı, Doğu Akdeniz bölgesinde yer alan büyük güçlerin perspektiflerini belirlemek amacıyla medya kaynakları, kitap bölümleri ve dergi makaleleri gibi ikincil kaynaklara bakılarak nitel analize dayanacaktır. Bu araştırmanın sınırlılığı, ABD'nin silah ambargosunu kaldırma kararının bölge içinde gerilimlerin erimesine yol açtığı veya Kıbrıs sorununa ilişkin çok daha dengeli bir dinamiğin ortaya çıktığı durumlarda alternatif hipotezlerin var olabileceğidir. Genel olarak bu tez, ABD dış politikasındaki son zamanlardaki değişimlerin Doğu Akdeniz bölgesindeki ülkeler arasındaki bölgesel ilişkileri nasıl şekillendirebileceğine dair içgörü sağlayacak ve olası gelecek senaryoları hakkında varsayımlar sağlayacaktır.
Master of Arts in Diplomacy and Conflict Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2024. Supervisor: Prof. Dr. Kudret Özersay.
Keywords: Thesis Tez; Political Science and International Relations Department; Diplomacy and Conflict Management; Politics and government--United States--Foreign Policy--Mediterranean Region; US Foreign Policy; Eastern Mediterranean Region; Cyprus; Foreign Policy Shifts